Application of spirobiindane-based microporous poly(ether sulfone)s as polymeric binder on solid alkaline exchange membrane fuel cells - Choi, Jieun; Kim, Man-Ho; Han, Jun Young; Chae, Ji Eon; Lee, Won Hee; Lee, Young Moo; Lee, So Young; Jang, Jong Hyun; Kim, Jin Young; Henkensmeier, Dirk; Yoo, Sung Jong; Sung, Yung-Eun; et al. (ELSEVIER SCIENCE BV, 2018)
In this report, we introduced spirobiindane group to poly(arylene ether sulfone) (PES) to build the structure of polymers with intrinsic microporosity (PIMs). A novel PESs (QOH-SBIs), which have spirobiindane and tetra (quaternary ammonium) hydroxide pendant moieties, were synthesized for anion-conducting binder material in membrane electrode assembly (MEA) of solid alkaline exchange membrane fuel cell (SAEMFC). The time-lag method was used to check the high gas permeability of the polymers. The high permeability is due to the micro-pores at the molecular level that is formed by the difference in chain thicknesses between two alternating units, thick spirobiindane group and thin arylene ether sulfone group. QOH-SBIs shows a semi-rigid chain conformation in a solution. The inter-chain spacing and chain conformation were measured with wide angle X-ray diffraction (WAXD) and small angle neutron scattering (SANS), respectively. High gas permeability directly affected the performance of SAEMFC. The MEA with spirobiindane-modified PES shows much higher maximum power density than that of spirobiindane-free PESs.